Spin orientation in an exchange coupled Fe/Cr/Fe trilayer determined by polarized neutron reflection - Bland, J; Leung, H; Blundell, S; Speriosu, V; Metin, S; Gurney, B; Penfold, J (1996)
We have used polarized neutron reflection to determine the layer-dependent spin orientations in an antiferromagnetically coupled 100 Angstrom Cr/50 Angstrom Fe/15 Angstrom Cr/50 Angstrom Fe/Si sandwich structure prepared by sputtering. At low field, the net Fe layer magnetic moments align in an asymmetric canted orientation with a near zero total magnetic moment for the sample. At high fields, a canted state, nearly symmetric with respect to the applied field direction is observed and the magnetization in each layer does not reach the bulk saturation value until the layers are ferromagnetically aligned. The behavior is discussed in the context of current theories of exchange coupling. (C) 1996 American Institute of Physics.